A new dual-function fluorescent probe of Fe3+ for bioimaging and probe-Fe3+ complex for selective detection of CN−. Issue 29 (21st July 2016) - Yan, Lirun; Yang, Meipan; Leng, Xin; Zhang, Ming; Long, Ying; Yang, Bingqin
Abstract: A rhodamine-based probe for Fe 3+ was prepared and confirmed by X-ray crystallography. The probe exhibited highly selective and sensitive recognition toward Fe 3+ with distinct color change. Interestingly, the probe-Fe 3+ complex could detect CN − according to the strong co-ordination ability of cyanide to Fe 3+ . The whole recognition mechanism was explored through Job's plot, MS data and theoretical calculations. Importantly, the probe was further used for detecting Fe 3+ in living cells and mouse, which exhibited excellent fluorescence imaging. Graphical abstract: